Modulation of human dendritic-cell function following transduction with viral vectors: implications for gene therapy - Tan, Peng H.; Beutelspacher, Sven C.; Xue, Shao-An; Wang, Yao-He; Mitchell, Peter; McAlister, James C.; Larkin, D. Frank P.; McClure, Myra O.; Stauss, Hans J.; Ritter, Mary A.; Lombardi, Giovanna; George, Andrew J. T. (Blood, 2005)
Genetic modification of dendritic-cell (DC) function is an attractive approach to treat disease, either using mature DCs (mDCs) to immunize patients, or immature DCs (iDCs) to induce tolerance. Viral vectors are efficient at transducing DCs, and we have investigated the effect of transduction with a variety of viral vectors on the phenotype and function of DCs. Adenovirus (Ad), human immunodeficiency virus (HIV), equine anemia virus (EIAV), and Moloney murine leukemia virus (MMLV) all up-regulate costimulatory molecules and major histocompatibility complex (MHC) class II expression on DCs, as well as, in the case of Ad and lentiviral vectors, inducing production of Th1 and proinflammatory cytokines. Following transduction there is activation of double-stranded (ds) RNA-triggered pathways resulting in interferon (IFN) α/β production. In addition, the function of virally infected DCs is altered; iDCs have an increased, and mDCs a decreased, ability to stimulate a mixed lymphocyte reaction (MLR). Viral transduction of mDCs results in up-regulation of the indoleamine 2,3-dioxygenase (IDO) enzyme, which down-regulates T-cell responsiveness. Inhibition of IDO restores the ability of mDCs to stimulate an MLR, indicating that IDO is responsible for the modulation of mDC function. These data have important implications for the use of viral vectors in the transduction of DCs.